Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7860/jcdr/2020/44408.13968
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Glycated Haemoglobin by Nephelometry, Ion Exchange Resin and High Performance Liquid Chromatography: A Cross-sectional Study

Abstract: Introduction: Diabetes mellitus cases are continually rising all over the world. Glycated haemoglobin (HbA1c) used as a diagnostic test to measure long-term average glycaemic control in diabetic patients. Aim: To assess the precision and reproducibility of the Ion Exchange Column Chromatography Resin (IECR) method and nephelometry in comparison to High-Performance Liquid Chromatography (HPLC) with respect to the estimation of HbA1c. Materials and Methods: A cross-sectional comparative study was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…The irregular arrangement of Cs chains can be seen in the CsNPs XRD spectrum, showing a large diffuse hump peak at 20°, which is a typical semicrystalline Cs fingerprint. The current study's findings agree with an old study 24 that demonstrated that the TPP counter-ions cause cross-linking between Cs chains, leading to an opaque network structure which removed the Cs diffraction peaks and created that single floppy peak. The presence of a broad peak, on the other hand, meant a reduction in crystallite size, indicating a lower periodicity and a reduction in the ordering of hkl planes, i.e., a reduction in crystallinity.…”
Section: Xrd Analysissupporting
confidence: 91%
“…The irregular arrangement of Cs chains can be seen in the CsNPs XRD spectrum, showing a large diffuse hump peak at 20°, which is a typical semicrystalline Cs fingerprint. The current study's findings agree with an old study 24 that demonstrated that the TPP counter-ions cause cross-linking between Cs chains, leading to an opaque network structure which removed the Cs diffraction peaks and created that single floppy peak. The presence of a broad peak, on the other hand, meant a reduction in crystallite size, indicating a lower periodicity and a reduction in the ordering of hkl planes, i.e., a reduction in crystallinity.…”
Section: Xrd Analysissupporting
confidence: 91%
“…The components of the HPLC system included a mobile phase buffer for hemolysis & wash solution, elution buffer, and a stationary phase chromatography column. Although there are a number of studies evaluating these analyzers or comparing different analyzers [ 27 ], few studies have evaluated the performance of mobile phase buffers or whether the diagnostic kit was suitable for certain analyzers. Although the analyzer plays an important role in the HPLC measurement system, the performance of the mobile phase buffer is also crucial for the reliability of the HbA1c assay [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…the impact of continuous increase in FBS can be seen in progressive glycation of glucose to haemoglobin, as is reflected by values obtained for HbA1c which were significant as compared to control. This changes could be due to the dysregulation of glucose [12,13]. Increase in HbA1c as seen in (Table 1) suggest serves as an indicator of blood glucose control,and a marker of diabetes [14].…”
Section: Metabolic and Immunologic Parametersmentioning
confidence: 99%